Notes for Future Landscapes or Screaming Reliefs (Palíndromo, 2025)
This speculative field essay presents the artistic operation of (a)notation as a poetic methodology between writing and listening to the Earth. Through a text that drifts between an academic and a fictional format, we see a stone that cries out in the silence of its immensity, and multiple future landscapes that erupt at the speculation of how to read a resounding relief. Nevertheless, different notes pose problems for the reader about attention (in a disconnected world), inscription (in a codified world), and reporting (in an informational world), thus proposing a speculative twist on the traditional modes of scientific field notes, by positioning listening as a fundamental sense and practice for the writing of more sensitive and less anthropocentric impressions.
Keywords: Notation; Listening; Writing; Speculation; Reliefs